The Community Service Program for Assisting Bottled Coffee Production Through Packaging, Brand Labeling, and Web Based Marketing to Enhance the Economy of Dharmasraya Regency - Prasetyo, Dian Estu; Badri , Ainul; Sukron, Muhammad (The Future of Education Journal, 2025)
The development of MSMEs and home industries in Dharmasraya Regency is quite diverse; one of them is the processing of robusta ground coffee into bottled coffee beverages, which is still rarely practiced and not yet widely recognized by the public. People are more familiar with and tend to consume sachet and powdered coffee products marketed under various brands from outside the region. The first issue encountered is related to production constraints, particularly the limited ability of business owners to operate coffee grinder machines. Currently, they still rely on a mini grinder, which restricts the volume of bottled coffee produced and hinders business growth. The use of espresso machines is also limited, as processing is still carried out using a semi-automatic coffee maker. The second urgent issue concerns packaging. The bottled coffee products still use simple plastic bottles with minimally informative sticker labels, whereas ideally, the packaging should be more appealing, modern, and informative. The third urgent issue is the absence of registered labels and trademarks for the bottled coffee products, which creates obstacles in marketing, as the products cannot yet reach wider or out-of-region market segments. The fourth issue relates to marketing practices, which are still conventional and have not fully utilized digital technology or social media platforms, including websites. Promotion is currently conducted only through WhatsApp statuses and group shares, which has proven ineffective. Considering the high market potential for bottled coffee beverages in Indonesia, there is an opportunity for Dharmasraya’s bottled robusta coffee to be marketed nationally through the use of website-based technology. These major challenges must be addressed to improve the performance of home-based coffee beverage industries. Therefore, assistance in the form of mentoring for bottled coffee production covering packaging, brand labeling, and web-based marketing is urgently needed to boost sales of Dharmasraya’s robusta bottled coffee products. The low sales volume is also a result of limited marketing, which is still confined to local stalls and shops and has not yet utilized website-based promotion. Web-based marketing is expected to expand entrepreneurs’ knowledge and enable them to maximize digital technology as a more effective promotional tool at national and even international levels, ultimately improving the sales performance of bottled coffee products in Dharmasraya.